High polymer reinforced nano carbon material-metal composite material and preparation method thereof
By introducing polymeric compounds into nanocarbon materials and metal composites, polymer-enhanced nanocarbon materials-metal composites are formed, which solves the problem of insufficient thermal conductivity, hardness and thermal expansion performance of traditional pipeline materials, and achieves higher thermal conductivity, hardness and thermal expansion performance, which is suitable for high-demand industrial applications.
Patent Information
- Application Number
- CN202510050755.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing pipeline materials have shortcomings in thermal conductivity, hardness and thermal expansion performance, resulting in untimely heat transfer, easy deformity of the material and loose joints, affecting the efficiency and safety of industrial processes.
The nanocarbon material and metal composite materials are modified by polymer compounds to form polymer-enhanced nanocarbon material-metal composite materials to improve their thermal conductivity, hardness and thermal expansion properties.
It significantly improves the thermal conductivity, hardness and thermal expansion properties of nano-carbon materials and metal composite materials, enhances the overall performance of the material, and is suitable for industrial applications of high temperature, high pressure and high efficiency heat exchange.
Smart Images

Figure BDA0005239885030000051 
Figure BDA0005239885030000061 
Figure BDA0005239885030000062
Abstract
Description
Technical Field
[0001] The invention relates to the field of nano carbon materials, and in particular to a polymer reinforced nano carbon material-metal composite material and a preparation method thereof. Background Art
[0002] Pipeline systems play a vital role in many industrial fields such as petrochemicals, energy transportation, heating and cooling. They are responsible for the transportation of fluids or gases, and their performance directly affects the efficiency, safety and reliability of the entire industrial process. As modern industry develops towards high temperature, high pressure, and high efficiency, higher and higher requirements are placed on the thermal conductivity, hardness, and thermal expansion properties of pipeline materials. Traditional pipeline materials have gradually exposed many limitations in response to these challenges, and the emergence of carbon nanotubes has brought new opportunities for improving pipeline performance. As a nanomaterial with excellent performance, carbon nanotubes have a unique structure that gives them excellent properties in mechanics, electricity, heat, and chemistry.
[0003] Many traditional pipeline materials, such as ordinary carbon steel, stainless steel and other metal materials, have a certain thermal conductivity, but the thermal conductivity is relatively limited. In some application scenarios that require efficient heat dissipation or rapid heat transfer, such as high-temperature steam transmission pipelines, heat exchanger pipelines, etc., this low thermal conductivity will cause the heat to not be dissipated or transferred in time, resulting in energy loss and local overheating of the pipeline, affecting the service life of the pipeline and the operating efficiency of the system. Non-metallic pipeline materials such as plastic pipes (such as polyethylene, polypropylene, etc.) have lower thermal conductivity, usually between 0.2-0.5W / (m·K). In pipeline applications involving heat exchange with the outside world, the low thermal conductivity of plastic pipes will seriously hinder the transfer of heat, making the heat exchange process slow and insufficient, and unable to meet some industrial needs with high requirements for heat exchange efficiency.
[0004] Traditional metal pipe materials have certain deficiencies in terms of hardness. For example, the hardness of ordinary carbon steel is relatively low, and its Brinell hardness is generally between 150-200HB. It is easy to deform, scratch or corrode when subjected to external impact, wear or high-pressure fluid scouring. When conveying fluids containing solid particles or under high flow conditions, the inner wall of the carbon steel pipe is easily worn, resulting in thinning of the pipe wall thickness, reducing the load-bearing capacity and safety of the pipe. Although some alloy materials such as chromium-molybdenum alloy steel have higher hardness, they are often accompanied by problems such as high cost and difficulty in processing.
[0005] Metal pipe materials will expand when the temperature changes. For example, the linear expansion coefficient of carbon steel is about 10-12×10 -6 / ℃, the linear expansion coefficient of stainless steel is 16-18×10 -6 / ℃. In applications where long-distance pipeline transportation or frequent large temperature changes occur, such as geothermal pipelines and chemical reaction pipelines, this thermal expansion will produce large thermal stress. If the thermal expansion of the pipeline is not effectively compensated, it may cause pipeline deformation, loose joints or even rupture, leading to leakage accidents and causing serious harm to industrial production and the environment. Non-metallic pipeline materials also have thermal expansion problems, and the thermal expansion coefficient of some plastic pipelines is larger than that of metals.
[0006] In view of the problems existing in the prior art, this application aims to solve the problems of insufficient thermal conductivity, hardness and thermal expansion performance of pipeline materials. Summary of the invention
[0007] Purpose of the invention: The purpose of the present invention is to provide a polymer reinforced nano-carbon material-metal composite material and a preparation method thereof, wherein the nano-carbon material and the metal composite material are modified by a polymer compound, and the polymer compound improves the strength and modulus of the nano-carbon material and the metal composite material, and improves the thermal conductivity, hardness and thermal expansion properties of the polymer reinforced nano-carbon material-metal composite material.
[0008] The technical solution of the present invention:
[0009] The present invention provides a polymer reinforced nano-carbon material-metal composite material, characterized in that the raw materials of the polymer reinforced nano-carbon material-metal composite material include, by weight, 40-70 parts of nano-carbon material, 20-50 parts of metal composite material, 5-10 parts of polymer compound and 1-3 parts of reinforcing auxiliary agent.
[0010] Furthermore, the nano-carbon material is a mixture of one or more of nano-carbon tubes, nano-carbon spheres, and graphite.
[0011] Furthermore, the preparation of the metal composite material comprises the following steps:
[0012] S1: adding metal powders in a certain proportion into a ball mill, adding an appropriate amount of ethanol for ball milling and mixing, ball milling for 0.5-1 hour to obtain a uniformly mixed metal composite powder, drying the metal composite powder in a vacuum drying oven at a drying temperature of 40-60°C, and removing the ethanol for later use;
[0013] S2: mixing the metal composite powder dried in step S1 with phenolic resin in a certain ratio, and kneading them in a mixer to obtain a kneaded mixture;
[0014] S3: placing the kneaded mixture prepared in step S2 into a mold, and performing hot pressing molding on a hot press, the hot pressing temperature is 180-200° C., the pressure is 20-30 MPa, and the holding time is 1-2 hours;
[0015] S4: Sintering the sample formed by hot pressing in step S3 in a nitrogen atmosphere at a sintering temperature of 1600-1800° C. for a heat preservation time of 2-3 hours to obtain a metal composite material.
[0016] Furthermore, the metal powder in step S1 is a mixture of one or more of nickel, chromium, titanium, silver, tungsten, molybdenum and manganese.
[0017] Furthermore, in step S2, the mass ratio of the metal composite powder to the phenolic resin is 3-5:1.
[0018] Furthermore, the preparation of the polymer compound comprises the following steps:
[0019] S1: Add 2-hydroxybenzaldehyde and dimethylformamide into a three-necked flask, then add aspartic acid and tetrabutyl titanate, and stir evenly;
[0020] S2: raising the temperature of step S1 to 100-120°C for 10-16 hours;
[0021] S3: After the reaction in step S2 is completed, the reaction solution is cooled to room temperature and then poured into cold water to precipitate the polymer. The polymer precipitate obtained is filtered, washed with deionized water, and then dried in a vacuum drying oven to constant weight at a drying temperature of 50-60°C and a drying time of 12-24 hours to obtain a polymer compound.
[0022] Furthermore, the mass ratio of the 2-hydroxybenzaldehyde to aspartic acid is 0.8-1:1.
[0023] Furthermore, the addition amount of tetrabutyl titanate is 2-5% of the total mass of 2-hydroxybenzaldehyde and aspartic acid.
[0024] Furthermore, the strengthening aid is a mixture of one or more of silicon dioxide, calcium oxide and calcium sulfate.
[0025] The present invention also provides a method for preparing a polymer reinforced nano-carbon material-metal composite material, which is characterized by comprising the following steps:
[0026] (1) adding nano-carbon materials into a reaction kettle, and then adding an acidic mixed solution to pretreat the nano-carbon materials;
[0027] (2) adding the nano-carbon material, metal composite material and strengthening agent pretreated in step (1) into chlorosulfonic acid, controlling the temperature at 0-10° C. and stirring for 1-3 hours to form a uniform composite carbon nanotube dispersion;
[0028] (3) adding the polymer compound to the composite carbon nanotube dispersion prepared in step (2), stirring and mixing to form a uniform spinning solution;
[0029] (4) pouring the prepared spinning solution into a liquid storage tank of a spinning device, and extruding it into a coagulation bath through a spinneret for wet spinning;
[0030] (5) subjecting the fiber obtained by wet spinning in step (4) to high-temperature carbonization treatment under the protection of an inert atmosphere;
[0031] (6) After the high-temperature carbonization treatment in step (5), the temperature is raised again and then kept warm for a period of time to obtain the polymer reinforced nano-carbon material-metal composite material.
[0032] Furthermore, the acidic mixed solution in step (1) is a mixture of concentrated sulfuric acid and concentrated nitric acid.
[0033] Furthermore, the mass ratio of the acidic mixed solution to the nano-carbon material is 5-10:1.
[0034] Furthermore, in step (3), the stirring speed is 500-1500 rpm and the stirring time is 3-6 hours.
[0035] Furthermore, the coagulation bath in step (4) is an aqueous solution of water and inorganic salts, the temperature is 20-40° C., the extrusion pressure is 0.1-0.5 MPa, and the drawing speed is 1-5 m / min.
[0036] Furthermore, the inorganic salt in step (4) is one or more of calcium chloride and sodium sulfate.
[0037] Furthermore, in step (5), the heating rate is 5-10°C / min, the carbonization temperature is 800-1500°C, and the insulation time is 1-3 hours.
[0038] Furthermore, the step (6) is further heated to a temperature of 2000-3000° C. and a heat preservation time of 0.5-2 hours.
[0039] The present invention provides a polymer reinforced nano-carbon material-metal composite material, in which the polymer compound is cross-linked between the nano-carbon material and the metal composite material to increase its elongation at break, and after carbonization, its benzene ring structure further improves the thermal conductivity, hardness and thermal expansion performance of the nano-carbon material and the metal composite material.
[0040] Beneficial effects:
[0041] The invention provides a polymer reinforced nano-carbon material-metal composite material. The polymer reinforced nano-carbon material-metal composite material has high thermal conductivity, hardness and good thermal expansion performance and has good application prospects. DETAILED DESCRIPTION
[0042] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0043] Unless otherwise specified, the chemical reagents used in the present invention are all commercially available analytically pure; the phenolic resin model is BMJ-92, purchased from Ruibo Chemical Co., Ltd.
[0044] Preparation of metal composite materials:
[0045] S1: 1 kg of nickel powder, 0.5 kg of chromium powder and 0.5 kg of titanium powder were added into a ball mill, and 5 L of ethanol was added for ball milling and mixing. The mixture was ball milled for 0.5 hours to obtain a uniformly mixed metal composite powder. The metal composite powder was dried in a vacuum drying oven at a drying temperature of 50°C, and the ethanol was removed for later use;
[0046] S2: adding 0.4 kg of phenolic resin to the metal composite powder dried in step S1 according to a certain ratio, and mixing in a mixer to obtain a mixed mixture;
[0047] S3: placing the kneaded mixture prepared in step S2 into a mold, and performing hot pressing molding on a hot press, the hot pressing temperature is 180° C., the pressure is 25 MPa, and the holding time is 2 hours;
[0048] S4: Sintering the sample formed by hot pressing in step S3 in a nitrogen atmosphere at a sintering temperature of 1800° C. for a heat preservation time of 2 hours to obtain a metal composite material.
[0049] Preparation of polymer compound A:
[0050] S1: Add 1 kg of 2-hydroxybenzaldehyde and 1 L of dimethylformamide into a three-necked flask, then add 1 kg of aspartic acid and 0.04 kg of tetrabutyl titanate, and stir evenly;
[0051] S2: Heat the reaction in step S1 to 120°C for 12 hours;
[0052] S3: After the reaction in step S2 is completed, the reaction solution is cooled to room temperature and then poured into cold water to precipitate the polymer. The polymer precipitate obtained is filtered, washed with deionized water, and then dried in a vacuum drying oven to constant weight at a drying temperature of 50° C. for 24 hours to obtain a polymer compound.
[0053] Preparation of polymer compound B:
[0054] The difference between the present preparation and the polymer compound A is that 1 kg of 2-hydroxybenzaldehyde and 1 kg of aspartic acid in step S1 are replaced by 0.8 kg of 2-hydroxybenzaldehyde and 1 kg of aspartic acid.
[0055] Preparation of polymer compound C:
[0056] The difference between the present preparation and the polymer compound A is that 1 kg of 2-hydroxybenzaldehyde and 1 kg of aspartic acid in step S1 are replaced by 1.2 kg of 2-hydroxybenzaldehyde and 0.8 kg of aspartic acid.
[0057] Preparation of polymer reinforced nanocarbon-metal composites:
[0058] (1) adding nanocarbon materials into a reaction kettle, and then adding an acidic mixed solution (the mass ratio of concentrated sulfuric acid to concentrated nitric acid is 1:1) with a mass of 5 times the mass of the nanocarbon materials to pretreat the nanocarbon materials;
[0059] (2) adding the nano-carbon material, the metal composite material and the reinforcing agent pretreated in step (1) into chlorosulfonic acid with a mass 10 times that of the nano-carbon material and the metal composite material, controlling the temperature at 0° C. and stirring for 2 hours to form a uniform composite carbon nanotube dispersion;
[0060] (3) adding the polymer compound to the composite carbon nanotube dispersion prepared in step (2), stirring and mixing to form a uniform spinning solution, the stirring speed is 1000 rpm, and the stirring time is 5 hours;
[0061] (4) pouring the prepared spinning solution into a liquid storage tank of a spinning device, and extruding it through a spinneret into a coagulation bath for wet spinning, wherein the coagulation bath is an aqueous solution of water and calcium chloride (the mass ratio of water to calcium chloride is 10:1), the temperature is 20° C., the extrusion pressure is 0.25 MPa, and the drawing speed is 2 m / min;
[0062] (5) subjecting the fiber obtained by wet spinning in step (4) to high-temperature carbonization treatment under nitrogen protection, with a heating rate of 10° C. / min, a carbonization temperature of 1000° C., and a holding time of 2 hours;
[0063] (6) After the high-temperature carbonization treatment in step (5), the temperature is raised to 2500° C. and kept at this temperature for 1 hour to obtain the polymer-reinforced nano-carbon material-metal composite material.
[0064] Examples 1-4
[0065] According to the above-mentioned preparation method of polymer reinforced nano-carbon material-metal composite material, Table 1 is the ingredient list of polymer reinforced nano-carbon material-metal composite material of Examples 1-4 in parts.
[0066] Table 1:
[0067]
[0068]
[0069] Comparative Example 1-2
[0070] Comparative Examples 1-2 were prepared according to the above-mentioned method for preparing polymer reinforced nano-carbon material-metal composite materials. Table 2 is a list of ingredients of polymer reinforced nano-carbon material-metal composite materials of Comparative Examples 1-2 in parts.
[0071] Table 2:
[0072]
[0073] The polymer reinforced nano-carbon material-metal composite material prepared in Examples 1-4 and Comparative Examples 1-2 was prepared into The carbon tubes were tested for the following properties:
[0074] 1. Thermal conductivity test:
[0075] According to the standard GB / T 8722-2019 "Method for Determining Thermal Conductivity of Carbon Materials", the polymer reinforced nano-carbon material-metal composite materials prepared in Examples 1-4 and Comparative Examples 1-2 were prepared. The carbon tube samples were tested for thermal conductivity.
[0076] 2. Hardness test:
[0077] According to the standard GB / T 39535-2020 "High-temperature stress relaxation test method for high-temperature alloys", the polymer reinforced nano-carbon material-metal composites prepared in Examples 1-4 and Comparative Examples 1-2 were prepared. The carbon tube samples were subjected to hardness test.
[0078] 3. Thermal expansion coefficient test:
[0079] According to the standard JB / T 8133.18-2017 "Test methods for physical and chemical properties of electric carbon products Part 18: Linear expansion coefficient", the polymer reinforced nano-carbon material-metal composite materials prepared in Examples 1-4 and Comparative Examples 1-2 were prepared. The carbon tube samples were tested for thermal expansion coefficient.
[0080] Table 3: Test results
[0081]
[0082] From the above data, it can be seen that the carbon tubes prepared from the polymer-reinforced nano-carbon material-metal composite materials prepared in Examples 1-3 have high thermal conductivity, high hardness, small linear expansion coefficient, high stability, and will not produce excessive deformation due to thermal expansion and contraction; from the comparison between Example 4 and Example 2, it can be seen that adjusting the mass ratio of 2-hydroxybenzaldehyde and aspartic acid for preparing the polymer compound will cause the thermal conductivity of the carbon tubes of the prepared polymer-reinforced nano-carbon material-metal composite materials to deteriorate, reduce the hardness, and reduce the linear expansion coefficient; from the comparison between Comparative Example 1 and Example 2, it can be seen that without adding the polymer compound, the thermal conductivity of the carbon tubes prepared from the polymer-reinforced nano-carbon material-metal composite materials will deteriorate, the hardness will be reduced, and the linear expansion coefficient will be reduced; from the comparison between Comparative Example 2 and Example 2, it can be seen that when the metal composite material is not added, the thermal conductivity of the carbon tubes prepared from the polymer-reinforced nano-carbon material-metal composite materials will deteriorate, the hardness will be reduced, and the linear expansion coefficient will be reduced, and the expected effect will not be achieved.
[0083] The present invention can also have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.
Claims
1. A polymer reinforced nano-carbon material-metal composite material, characterized in that: The raw materials of the polymer reinforced nano carbon material-metal composite material include, by weight: 40-70 parts of nano carbon material, 20-50 parts of metal composite material, 5-10 parts of polymer compound and 1-3 parts of reinforcing auxiliary agent.
2. The polymer reinforced nano-carbon material-metal composite material according to claim 1, characterized in that: The nano-carbon material is a mixture of one or more of nano-carbon tubes, nano-carbon balls and graphite.
3. The polymer reinforced nano-carbon material-metal composite material according to claim 1, characterized in that: The preparation of the metal composite material comprises the following steps: S1: adding metal powders in a certain proportion into a ball mill, adding an appropriate amount of ethanol for ball milling and mixing, ball milling for 0.5-1 hour to obtain a uniformly mixed metal composite powder, drying the metal composite powder in a vacuum drying oven at a drying temperature of 40-60°C, and removing the ethanol for later use; S2: mixing the metal composite powder dried in step S1 with phenolic resin in a certain ratio, and kneading them in a mixer to obtain a kneaded mixture; S3: placing the kneaded mixture prepared in step S2 into a mold, and performing hot pressing molding on a hot press, the hot pressing temperature is 180-200° C., the pressure is 20-30 MPa, and the holding time is 1-2 hours; S4: Sintering the sample formed by hot pressing in step S3 in a nitrogen atmosphere at a sintering temperature of 1600-1800° C. for a heat preservation time of 2-3 hours to obtain a metal composite material.
4. The polymer reinforced nano-carbon material-metal composite material according to claim 3, characterized in that: The metal powder in step S1 is a mixture of one or more of nickel, chromium, titanium, silver, tungsten, molybdenum and manganese.
5. The polymer reinforced nano-carbon material-metal composite material according to claim 3, characterized in that: In step S2, the mass ratio of the metal composite powder to the phenolic resin is 3-5:
1.
6. The polymer reinforced nano-carbon material-metal composite material according to claim 2, characterized in that: The preparation of the polymer compound comprises the following steps: S1: Add 2-hydroxybenzaldehyde and dimethylformamide into a three-necked flask, then add aspartic acid and tetrabutyl titanate, and stir evenly; S2: raising the temperature of step S1 to 100-120°C for 10-16 hours; S3: After the reaction in step S2 is completed, the reaction solution is cooled to room temperature and then poured into cold water to precipitate the polymer. The polymer precipitate obtained is filtered, washed with deionized water, and then dried in a vacuum drying oven to constant weight at a drying temperature of 50-60°C and a drying time of 12-24 hours to obtain a polymer compound.
7. The polymer reinforced nano-carbon material-metal composite material according to claim 6, characterized in that: The mass ratio of the 2-hydroxybenzaldehyde to aspartic acid is 0.8-1:1; the addition amount of the tetrabutyl titanate is 2-5% of the total mass of the 2-hydroxybenzaldehyde and aspartic acid.
8. The polymer reinforced nano-carbon material-metal composite material according to claim 1, characterized in that: The strengthening auxiliary agent is a mixture of one or more of silicon dioxide, calcium oxide and calcium sulfate.
9. The method for preparing the polymer reinforced nano-carbon material-metal composite material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) adding nano-carbon materials into a reaction kettle, and then adding an acidic mixed solution to pretreat the nano-carbon materials; (2) adding the nano-carbon material, metal composite material and strengthening agent pretreated in step (1) into chlorosulfonic acid, controlling the temperature at 0-10° C. and stirring for 1-3 hours to form a uniform composite carbon nanotube dispersion; (3) adding the polymer compound to the composite carbon nanotube dispersion prepared in step (2), stirring and mixing to form a uniform spinning solution; (4) pouring the prepared spinning solution into a liquid storage tank of a spinning device, and extruding it into a coagulation bath through a spinneret for wet spinning; (5) subjecting the fiber obtained by wet spinning in step (4) to high-temperature carbonization treatment under the protection of an inert atmosphere; (6) After the high-temperature carbonization treatment in step (5), the temperature is raised again and then kept warm for a period of time to obtain the polymer reinforced nano-carbon material-metal composite material.
10. The method for preparing the polymer reinforced nano-carbon material-metal composite material according to claim 9, characterized in that: In step (1), the acidic mixed solution is a mixture of concentrated sulfuric acid and concentrated nitric acid; the mass ratio of the acidic mixed solution to the nano-carbon material is 5-10:1; The stirring speed in step (3) is 500-1500 rpm and the stirring time is 3-6 hours; The coagulation bath in step (4) is an aqueous solution of water and inorganic salts, the temperature is 20-40° C., the extrusion pressure is 0.1-0.5 MPa, and the drawing speed is 1-5 m / min; The inorganic salt in step (4) is one or more of calcium chloride and sodium sulfate; The heating rate of step (5) is 5-10°C / min, the carbonization temperature is 800-1500°C, and the holding time is 1-3 hours; The step (6) is to heat up again, the heating temperature is 2000-3000° C., and the heat preservation time is 0.5-2 hours.
Citation Information
Patent Citations
Preparation technology of metal nanometer fiber
CN105063804A
Flexible self-supporting microporous layer and preparation method and application thereof
CN117174918A
Preparation method of multi-wall nanometer carbon tube conductive material for switch contact device
CN1699283A
Flexible carbon fiber nonwoven fabric
US20120251925A1
Polyer / filler / metal composite fiber and preparation method thereof
US20160122908A1